The Efficacy and Safety of Brolucizumab for the Treatment of nAMD: A Systematic Review and Meta-Analysis - Chuan, Junlan; Liu, Lianqiao; Feng, Yumei; Wang, Mengdan; Li, Gang; Lv, Qin (Frontiers in Pharmacology, 2022)
Abstract Introduction Brolucizumab can be used to treat neovascular age-related macular degeneration (nAMD) because it antagonizes vascular endothelial growth factor (VEGF) in the vitreous, as demonstrated in pivotal clinical trials. However, brolucizumab may cause retinal vasculitis obliterans in the presence of inflammation in the eyes. In the present study, a meta-analysis of randomized controlled trials (RCTs) was conducted to evaluate the efficacy and safety of brolucizumab. Methods Clinic Trail.gov., Embase, Cochrane library, Pubmed were retrieved from inception until December 31th, 2021 for RCTs assessing the efficacy and safety of brolucizumab. Changes in Best Corrected Visual Acuity (BCVA), and Central Sub-Field Thickness (CSFT), incidence of adverse events, serious adverse events and serious ocular adverse events were extracted from eligible RCTs. Meta-analysis was performed using Revman 5.4.1. Results Six RCTs with 3574 participants were finally involved in this meta-analysis. The changes of BCVA were not statistically significant different between brolucizumab treated group and aflibercept group. Brolucizumab induced higher CSFT reduction compared with control agent (aflibercept). The incidence of adverse events was similar between brolucizumab group and control group (OR 0.63, 95% CI 0.37 to 1.08, P=0.09), and brolucizumab caused less serious adverse events (OR 0.78, 95% CI 0.63 to 0.95, P=0.01). However, brolucizumab could lead to more serious ocular adverse events than lucentis and aflibercept (OR 2.15, 95% CI 1.11 to 4.16, P=0.02). Conclusion Brolucizumab was non-inferior to other anti-VEGF agents in improving BCVA and decrease CSFT. But it caused more serious ocular adverse events which is worthy of special attention by ophthalmologists.